Look to the past for an optimistic future. Issue 6 (12th October 2017) - O'Dea, Aaron; Dillon, Erin M.; Altieri, Andrew H.; Lepore, Mauro L.
Abstract : Article impact statement : With greater integration between paleontologists and conservationists, the fossil record can be a positive force in conservation.